Kepemimpinan Islam Di Sektor Publik - Hidayat, Hidayat; Tumulo, Lukman j. (Asosiasi Ahli Administrasi Indonesia, 2021)
This research is a literature research that aims to find out and analyze how Islamic leadership in the public sector, for the realization of a trustworthy and responsible governance. This research is a qualitative research that is library research which uses books and other literatures as the main object. Based on the results of the study, it was found that Islamic leadership in the public sector was closely related to the figure of the Prophet Muhammad Saw. which is reflected in the traits: shiddiq, amanah, fathonah, tablig, wasathan, istiqomah in carrying out the wheels of leadership. Leaders have the overall task of running the wheels of their organization in order to create governance that is able to create security and comfort for all those they lead.